New-Onset Depression Following Hip Fracture Is Associated With Increased Length of Stay in Hospital and Rehabilitation Centers - Anna C. Phillips; Jane Upton; Douglas Carroll; Niharika Arora Duggal; Janet M. Lord (SAGE Open, 2015)
This article examines the coincident effects of new-onset depression post hip fracture on length of hospital stay, readmission rates, and incidence of infections in older adults. Participants were 101 hip fracture patients aged 60+ years; 38 developed depressive symptoms following their fracture. Infection rates, readmissions to hospital and rehabilitation units, and length of hospital stay were assessed over the 6 months post hip fracture from hospital and general practitioner notes. Patients who developed depression by Week 6 post fracture were likely to spend more time in hospital/rehabilitation wards ( p = .02) and more likely to be discharged to a rehabilitation unit ( p < .05). There were no group differences in readmissions or infection rates. New-onset depression coincident with hip fracture in older adults is associated with longer hospital ward stays and greater need for rehabilitation.